Effectiveness of the application of a specialized dictionary in the teaching of Biology in English - Ishmuratova М.Yu.; Kalizhanova, A.N.; Erezhep, A.A.; Shelestova, T.Yu. (Fundamental and Experimental Biology, 2020)
In Kazakhstan, in the process of transition the education to updated content, there is a problem of providing biology classes with the necessary materials in English. At the school and university level, there is a lack of textbooks, manuals and trilingual dictionaries on Biology. This aspect does not allow to learn successfully biology in English, to understand translation of terms, to translate in English. In present article materials on studying of application’s efficiency of the using trilingual dictionary (English-Russian-Kazakh, Russian-Kazakh-English and Kazakh-English-Russian) in senior high school are stated. The effectiveness of the tri-lingual dictionary on zoology in additional Biology classes in English was evaluated. The results of the studies show that the application of the trilingual dictionary in Biology lessons reliably increases the level of understanding of specialized texts and translation of scientific materials. The use of the dictionary on zoology increases the efficiency of translation from English to Russian and from Russian to English, reduces the time required for translation.